The Blood Glucose Changes Following Third Molar Surgery - Sharifi, Reza; Hasheminasab , Mahboube; Bolandparva, Farzaneh; Aboutalebi, Zahra; Ghasemi, Tayebeh (Regeneration, Reconstruction & Restoration (Triple R), 2021)
Introduction: Surgical removal of third molars has been well- known for causing stressful situation for the majority of the patients. Increasing serum glucose level is expected following acute rise in epinephrine level or probably local anesthetic injection. This study was designed to compare blood glucose levels before and after third molar surgery. Materials and Methods: In this prospective clinical trial study, candidates for third molar removal surgery were enrolled. Blood glucose level was measured by glucometer before and 10 minutes after surgery in each patient and the result were compared. Results: The mean blood glucose in 92 patients before the procedure were 110.82±15.38 mg/dl and after surgery, it increased significantly to 123.95±16.87 mg/dl (P<0.001). The only variable that effects the blood glucose level in this study was the type of local anesthetic (P = 0.019). Conclusion: The current study showed that there is a significant increase in blood glucose level in patients undergoing surgical removal of impacted third molar teeth.